An Introduction to Marco Reggio’s Activism and Research - Suleiman McShane; Erin Clancy (Humanimalia)
This introduction situates Marco Reggio as a significant critical voice in the Italian animal liberation movement and provides context for the English translation of the first chapter of his 2022 book Cospirazione animale. It outlines Reggio’s intersecting commitments to anti-speciesism, queer and trans-feminist theory, disability studies, and anti-colonial activism. Through a discussion of Reggio’s work on the contradictions within animal advocacy—exemplified by the case of Agitu Ideo Gudeta and the politics of “happy meat”—the introduction highlights his emphasis on embracing discomfort, provisionality, and intersectionality as necessary elements of multispecies justice. It also reviews Reggio’s broader contributions: his theoretical and editorial collaborations, his focus on vegephobia, the right-wing appropriation of animal advocacy, the practice of archiving animal resistance, and the role of sanctuaries as sites of care and coalition. Concluding with a reflection on the challenges of building truly intersectional and transformative movements, the introduction positions Reggio’s work as an invitation to navigate the tensions between solidarity, critique, and collective struggle.